2009
DOI: 10.1088/0022-3727/42/17/175404
|View full text |Cite
|
Sign up to set email alerts
|

Comparative investigation of fracture behaviour of aluminium-doped ZnO films on a flexible substrate

Abstract: The differences in the fracture behaviour of aluminium-doped ZnO (AZO) films on a flexible substrate subjected to tensile and compressive strains were investigated by using a simple-support bending method. It is found that the crack density and the crack spacing of the AZO films become saturated both in the face-out (FO) and in the face-in (FI) bending tests when the applied strain reaches a certain value. The saturated crack density of the AZO film in the FO bending is higher than that of the film in the FI b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…Both curves show a hysteresis. This behavior has most likely nothing to do with a changing band structure but more with cracks that appear perpendicular to the applied strain as observed for both ITO [17,49] and ZnO [18,21,50]. Piezoelectricity of ZnO:Al should not be an important effect because it needs an inhomogeneous strain field which is not the case for our experiments [21].…”
Section: Compared To Figs 3 and 4)mentioning
confidence: 77%
“…Both curves show a hysteresis. This behavior has most likely nothing to do with a changing band structure but more with cracks that appear perpendicular to the applied strain as observed for both ITO [17,49] and ZnO [18,21,50]. Piezoelectricity of ZnO:Al should not be an important effect because it needs an inhomogeneous strain field which is not the case for our experiments [21].…”
Section: Compared To Figs 3 and 4)mentioning
confidence: 77%
“…As a result, aluminum-zinc-oxide (AZO) and gallium-zinc-oxide (GZO) materials could become good alternatives to ITO because they have a low resistivity in the order of 10-4 Ω·cm despite being indium-free materials [5,6]. However, these materials still cannot be applied in large area, flexible substrates due to their polycrystalline structure [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [11] reported buckling experiments carried out on ITO, reporting that the crack onset strain (COS) of the film under tension at 1.1% was less than its value under compression. In addition, Ni et al [12] investigated the fracture properties of AZO-coated on PET substrates under simple-support bending conditions. It was reported that the coating damage, under tensile strain, is caused by the creation of channel cracks, while under compression the film specimen may first delaminate from the polymer substrate and then buckle before the initiation of a crack.…”
Section: Introductionmentioning
confidence: 99%